Climate change and aflatoxins exposure in Portugal: could be expect a significant health risk? - Assunção, Ricardo (2018)
INSA (Project BioMAN, BioMAN/DAN/01). CESAM (FCT_UID/AMB/50017/2013). FEDER (POCI-01-0145-FEDER-00763). PT2020 Partnership Agreement and Compete 2020.